PENALARAN DALAM PENELITIAN PENDIDIKAN ISLAM - Ginting, Nurman; Hasanuddin, Hasanuddin (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Reasoning has an important role in producing a conclusion from logical and analytical research activities. The process of searching and investigating which is an activity in research in collecting empirical data to explain a phenomenon requires good reasoning. Because reasoning is the ability to conclude based on evidence and describe it both in oral and written. In drawing these conclusions based on the truth propositions of the major premises, minor premises and the validity of drawing conclusions. In research, these propositions are contained in the concept or meaning that is used as a statement used in explaining the object in research. There are three types of reasoning, namely, abductive, deductive and inductive. While propositions according to their form are categorical propositions; hypothetical propositions; dysfunctional propositions.